Hemagglutinin expressed by yeast reshapes immune microenvironment and gut microbiota to trigger diverse anti-infection response in infected birds - Xie, Ruyu; Zhang, Huixia; Zhang, Han; Li, Changyan; Cui, Daqing; Li, Shujun; Li, Zexing; Liu, Hualei; Huang, Jinhai (Frontiers in Immunology, 2023)
The H5N8 influenza virus is a highly pathogenic pathogen for poultry and human. Vaccination is the most effective method to control the spread of the virus right now. The traditional inactivated vaccine, though well developed and used widely, is laborious during application and more interests are stimulated in developing alternative approaches. In this study, we developed three hemagglutinin (HA) gene-based yeast vaccine and our experimental results demonstrated that all of these vaccines elicited the humoral immunity, inhibited viral load in the chicken tissues, and provided partial protective efficacy due to the high dose of the H5N8 virus. Molecular mechanism studies suggested that, compared to the traditional inactivated vaccine, our engineered yeast vaccine reshaped the immune cell microenvironment in bursa of Fabricius to promote the defense and immune responses. Analysis of gut microbiota further suggested that oral administration of engineered ST1814G/H5HA yeast vaccine increased the diversity of gut microbiota and the increasement of Reuteri and Muciniphila might benefit the recovery from influenza virus infection. These results provide strong evidence for further clinical use of these engineered yeast vaccine in poultry.